Determination of size‐dependent metal distribution in dissolved organic matter by SEC‐UV/VIS‐ICP‐MS with special focus on changes in seawater. Issue 7 (1st March 2016) - Rathgeb, Anna; Causon, Tim; Krachler, Regina; Hann, Stephan
Abstract : Iron is an essential micronutrient for all marine organisms, but it is also a growth limiting factor as the iron concentrations in the open ocean are below 1 nmol/L in sea water iron is almost entirely bound to organic ligands of the dissolved organic matter fraction, which are mostly of unknown structure. The input from rivers was traditionally considered as less important due to estuarine sedimentation processes of the mainly colloidal iron particles. However, recent studies have shown that this removal is not complete and riverine input may represent an important iron source in the open ocean. In this context, iron transport by land‐derived natural organic matter (NOM), and dissolved organic matter (DOM) have been identified as carrier mechanisms for riverine iron. The aim of this work is to characterize complexes containing iron and other metals in waters simulating estuarine conditions in order to help understand which role iron‐DOM compounds play in the open ocean. A method based on size‐exclusion chromatography (SEC) with sequential UV/VIS and ICP‐MS detection was developed for investigation of DOM size distribution and for assessment of the size‐dependent metal distribution in NOM‐rich surface water. Furthermore, sample matrix experiments were also performed revealing a dependence of DOM size distribution upon seawater concentration and different compounds present in seawater. Finally, efforts toward determination of DOM size with standardization with typical SEC standards indicate that only relative comparisons are possible with this approach, and that the sample matrix composition strongly influences obtained results.